PENGUATAN PENDIDIKAN KARAKTER DI SEKOLAH DASAR KABUPATEN TABANAN BALI INDONESIA (Widyadari : Jurnal Pendidikan, 2020)
Quantitatively, this research is conducted at elementary schools in Tabanan Regency and aims to analyze the direct positive influence of: (a) local wisdom on the implementation of KDP (b) literacy on the implementation of KDP, (c) local wisdom and literacy simultaneously on the implementation of KDP. Qualitatively aims to: (a) describe an overview of KDP implementation, (b) formulate a strategy that is appropriate for KDP implementation. The survey research used the Mixed Methods Research method with the triangulation design model. The total population was 319 in 11 sub-districts of Tabanan Regency and a sample of 32 SD. Quantitative data used Multiple Regression Analysis assisted by SPSS 23.0 program, while qualitative data were analyzed descriptively qualitatively using the model of Miles and Huberman (1992). The results of quantitative data analysis: (a) local wisdom has a direct positive effect on the implementation of KDP (b) literacy has a direct positive effect on the implementation of KDP in, (c) local wisdom and literacy simultaneously have a direct positive effect on the implementation of KDP. Qualitative results, that (a) the implementation of KDP in SD in Tabanan Regency is not optimal due to various obstacles, including: lack of guidance by related agencies, schools do not yet have KDP Implementation Operational Guidelines, involvement of community leaders in KDP coaching in schools has not been carried out by most schools, there is no legal umbrella to empower local wisdom in the implementation of KDP; (b) school literacy activities have not been optimally implemented according to the provisions, this is due to the lack of library sarpras, schools do not have school literacy manuals, lack of guidance related to school literacy activities, and the use of information technology in school literacy activities is still lacking. Recommendations: (a) there needs to be a legal umbrella for empowering local wisdom in the implementation of KDP, (b) it is necessary to prepare an Operational Guidebook for KDP Implementation, (c) school literacy activities must be supported through empowerment and optimization of school library facilities, and (d) the seriousness of all parties to participate in the implementation of KDP in SD in Tabanan Regency.